Ecological citizen!? - Rolston, Holmes, 1932-2025, author; Ecological Citizen, publisher (Colorado State University. Libraries, 2020)
An ecological citizen is a citizen who is also ecological. But let's be more precise. Can you be a citizen of an ecology? Citizens belong to nation-states, and need a passport to leave and re-enter. You can't be a citizen of a forest or a grasslands. Or of the biosphere. Citizens wherever need ecosystem services. These goods are not provided by political or government sources. The air we breathe today was in China last week. Ecological citizens do have a major worry, the rise of the Anthropocene enthusiasts. Enter the civilized designer world. Now the citizens, at least the wealthy and high-tech ones, propose to choose and build their re-vamped ecology, their "synthetic Earth." But yearning for a sense of natural place is a perennial human longing, of belonging to a community emplaced on landscape. That should be, the desire of every ecological citizen.
Keywords: ecological citizen; national states; ecosystem services; public goods; climate change; Anthropocene Epoch